Land Conflict Between Companies and The Community in Pari Island, Thousand Islands - Wibisono, Gunawan; Sunarno, Sunarno (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This research examines the land conflict that has arisen between a company and the residents of Pari Island in the Thousand Islands. The research addresses the following research questions:  1) What has been the prevailing model for resolving land conflicts between the company and the community of Pari Island in the Thousand Islands up to this point? 2) What is the ideal concept of land ownership and usage envisioned by both the company and the residents of the Thousand Islands? The research employs a sociolegal research methodology.  Research Outcomes: 1) The author's analysis suggests that the prevailing approach to resolving land conflicts between the company and the Pari Island community in the Thousand Islands has largely relied on government administration and political conflict resolution, namely "Government Administration and Political Conflict Resolution. This category of conflict resolution can guide one's thought process towards government administration and political solutions through legislative decisions." The resolution was achieved through conflict resolution efforts involving the local government in a non-litigious manner, specifically through mediation where the government acts as the mediator. Mediation has occurred on three occasions, two of which were held at the village level and one at the district level. 2) In the ideal concept that the author intends to propose for addressing the issue of conflict, one of the essential approaches that should be incorporated is the conflict resolution approach. The concept of conflict resolution prioritizes non-violent methods as the final recourse. The objective is to address conflicts in a constructive manner, with the ultimate goal of meeting the requirements and needs of all parties involved. Mediation, carried out by the parties involved in the land dispute on Pari Island, represents one form of conflict resolution. However, if mediation has not yielded success thus far, it becomes imperative to explore alternative conflict resolution models. Among these alternatives are negotiation and facilitation